ANALISIS PENGARUH INFLASI, DIVIDEND PAYOUT RATIO, DAN DEBT TO EQUITY RATIO TERHADAP RISIKO SISTEMATIS (BETA) SAHAM PADA PERUSAHAAN YANG TERCATAT DI INDEKS SAHAM SYARIAH JAKARTA (JAKARTA ISLAMIC INDEX) PERIODE 2015-2019 - SUSENO SUSENO; Riska Annisa Nur Rokhmah; Susanti Budiastuti (Majalah Imiah Manajemen & Bisnis, 2021)
This research purpose to determine the effect of Inflation, Dividend Payout Ratio, and Debt to Equity Ratio to Systematic Risk (Beta) Stock in company listed on the Jakarta Islamic Index. The hypothesis of this research is that Inflation, Dividend Payout Ratio, and Debt To Equity Ratio have a significant effect to Systematic Risk (Beta) Stock in companies listed on the Jakarta Islamic Index. The population 50 companies and the number of samples 8 companies during the observation 2015- 2019. Beta of Stock are the dependent variable, while Inflation, Dividend Payout Ratio, and Debt to Equity Ratio as independent variables. This research use panel data regression of panel data method. The results of this research indicate that Inflation has no effect on Systematic Risk (Beta) Stock, while the Dividend Payout Ratio and Debt to Equity Ratio have a significant effect on Systematic Risk (Beta) Stock. Keywords : Inflation;Dividend Payout Ratio;Debt to Equity Ratio; Systematic Risk (Beta) Stock